Biometria e qualidade fisiológica de sementes de diferentes matrizes de Tabebuia chrysotricha (Mart. Ex A. DC.) Stand I. - Dos Santos, Fabiana Silva [UNESP]; De Paula, Rinaldo César [UNESP]; Sabonaro, Débora Zumkeller [UNESP]; Valadares, Jane [UNESP] (My University, 2009)
This study aimed to determine the variation in biometric and physiological quality traits of seeds proceeding from different mother trees of Tabebuia chrysotricha (Mart. ex. A. DC.) Standl. Biometric traits were determined for the size (length, width and thickness) and fresh matter of seed, in completely random design with eight replications of 50 units, the averages were compared by Scott-Knott test at 5% probability. To evaluate the physiological quality, initially the seed water content was obtained and tests of germination and of accelerated aging were conducted. The germination test was carried out under constant temperature of 25°C. For substrate two sheets of paper germitest were used. The characteristics evaluated were the percentage of germination and normal seedlings; speed germination index; peak value and mean daily germination; germination value; length and dry weight of seedlings and percentage of seed polyembryony; for these tests eight replications of 25 seeds per treatment were used. The accelerated aging test was conducted at 45°C for 72 hours, using four replications of 25 seeds; the seed water content was determined, as was the percentage of normal seedlings in the germination test. The statistical design was completely randomized and the means were compared by Scott-Knott test at 5% probability. Estimates of correlation coefficients were obtained between the traits evaluated. The results indicate the existence of significant variation be tween the mother trees for the biometric and seed quality traits. The use of seed obtained from a small number of mother trees can compromise the genetic representation of the species; the mixture of seeds obtained from different mother trees represented a good estimate of average behavior of the population.
Biometric and physiological quality of Tabebuia chrysotricha (Mart. ex A. DC.) Standl. seeds from different mother trees
Keywords: Brazilian native trees; Forest seeds; Seeds vigor; Accelerated aging; Accelerated aging test; Average behavior; Biometric traits; Constant temperature; Correlation coefficient; Dry weight; Genetic representations; Germination index; Germination test; Peak values; Seed quality; Statistical design; Biometrics; Paper sheeting; Population statistics; Probability density function; Quality control; Statistical tests; Water content; Seed; Germination; Moisture Content; Physiology; Quality Control; Seeds; Statistical Analysis; Tabebuia; Trees